Analyzing the Social Burdens and Free Choices in Shaping the Character of Janie Crawford in the Novel "Their Eyes Were Watching God" (Journal of Asian Development Studies, 2024)
This research paper dissects the character of Janie Crawford, whose life is seen under the influence of social burdens and free choices. Using qualitative data, a mix of analytical and descriptive approaches is employed to analyze the text by closely reading it. Research shows that marriages are significant events in Janie's life, mainly showing the social burdens she faces and the free choices she makes. Her first two marriages' circumstances show how she was living by carrying the social burdens; moreover, her being a black slave woman is also the factor of society's labels that shape her journey. While the life and marriage with Tea Cake and life after him are counted under the umbrella of free choices, she made. In conclusion, Janie's character is seen as the outcome of both social burdens and, later, her realization of her freedom and independence in making her own decisions for her own life. Furthermore, her choices are seen as more potent in shaping her identity than societal ideals.